Testing the role of trade on carbon dioxide emissions in Portugal - Nuno Carlos Leit\~ao (Economies, 2021)
This article considers the relationship between trade intensity, energy consumption, income per capita, and carbon dioxide emissions from 1970-2016 for the Portuguese economy. Considering the arguments of monopolistic competition, the article tests the hypotheses of trade and energy consumption on climate change. We use the autoregressive distributed lag-ARDL model, quantile regression, and cointegration models such as fully modified ordinary least squares (FMOLS), canonical cointegration regression, and dynamic ordinary least squares (DOLS) as an econometric strategy. The econometric results have support with the literature review. The variables used in this research are integrated with the first differences, as indicated by the unit root test. The empirical study proves that trade intensity contributes to environmental improvements. However, energy consumption presents a positive impact on CO2 emissions. The econometric results also demonstrated that a sustainable environmental system exists in the long run.
Keywords: 330; Portugal; ARDL model; quantile regressions; cointegration models; trade; carbon dioxideemissions